DIAGNOSTIC TEST OF TORONTO AND MODIFIED TORONTO SCORING, MONOFILAMENT TEST, AND VIBRATE SENSATION TEST USING 128 HZ TUNING FORK FOR DIABETIC POLYNEUROPATHY - Purbasari, Bethasiwi; Anggraini, Vivi Laras; Pratiwi, Made Dinda; Husna, Machlusil; Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2018)
Background. The prevalence of diabetes mellitus has been epidemically increasing throughout all the world population, and diabetic polyneuropathy (PNP-DM) is one of the most common neurologic manifestation of this disease. Clinical research has proved that effective bedside screening of PNP-DM can significantly reduce the incidence of foot ulcer and limb amputation. Objective. To measure the diagnostic test of polyneuropathy scoring, monofilament 10-g SemmesWeinsteinÂ test, and 128 Hz tuning fork test as an early detection measure for PNP-DM.Methods. This research was conducted using a cross sectional approach from Januari 2016 to Juli 2017.Results. Among the total study population of 43 (23 men and 20 woman), Modified Toronto Score has the highest sensitivity (100%), PPV (93%) and accuracy (93%). Toronto score has the highest NPV (9%).Conclusion. Modified Toronto Score has good diagnostic value as screening tool in PNP-DM.